2017
DOI: 10.1177/0886260516681879
|View full text |Cite
|
Sign up to set email alerts
|

Physical Intimate Partner Violence and Controlling Behavior in Mexican University Students and Their Attitudes Toward Social Limits

Abstract: This study explored patterns of controlling behavior, physical violence, and attitudes toward social limits in young Mexican university students in light of the effect that socialization processes have in attitudes toward social norms and violent behavior as indicated in some of the literature. A total of 437 male and female heterosexual participants residing in Ciudad Juárez, Mexico, provided information on their perpetration/victimization experiences of controlling behavior (by means of the Controlling Behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 37 publications
3
7
0
2
Order By: Relevance
“…These findings are consistent with research that has found no direct link between psychological aggression and violent attitudes (e.g., Esquivel-Santoveña et al, 2020). IPV victimization for men and women that is predicted by their own perpetration experiences is consistent with the findings of research with dating samples reported elsewhere (Esquivel-Santoveña et al, 2020;Haynie et al, 2013;Orpinas, Nahapetyan, Song, McNicholas, & Reeves, 2012). Implications for male victimization and a widespread use of psychological aggression suggest that young educated men may struggle with power loss experiences that stem from traditional socialization processes, in light of the emergence of new masculinities.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are consistent with research that has found no direct link between psychological aggression and violent attitudes (e.g., Esquivel-Santoveña et al, 2020). IPV victimization for men and women that is predicted by their own perpetration experiences is consistent with the findings of research with dating samples reported elsewhere (Esquivel-Santoveña et al, 2020;Haynie et al, 2013;Orpinas, Nahapetyan, Song, McNicholas, & Reeves, 2012). Implications for male victimization and a widespread use of psychological aggression suggest that young educated men may struggle with power loss experiences that stem from traditional socialization processes, in light of the emergence of new masculinities.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, the findings here support the general belief that it is a pattern of dominance over a dating partner (rather than attitudes about violence) that better explains psychological aggression perpetration experiences for both men and women. These findings are consistent with research that has found no direct link between psychological aggression and violent attitudes (e.g., Esquivel-Santoveña et al, 2020). IPV victimization for men and women that is predicted by their own perpetration experiences is consistent with the findings of research with dating samples reported elsewhere (Esquivel-Santoveña et al, 2020;Haynie et al, 2013;Orpinas, Nahapetyan, Song, McNicholas, & Reeves, 2012).…”
Section: Discussionsupporting
confidence: 90%
“…However, it is important to notice that intimate partner violence is a complex and heterogeneous phenomenon and that there may be variations in gender rates of victimization and perpetration between different samples. In this sense, research data has shown that in a sample of university students controlling behavior is practiced about equally by men and women (Esquivel-Santoveña, Hernández, Viveros, Orozco, & van Barneveld, 2020).…”
Section: Controlling Behaviormentioning
confidence: 99%
“…Respecto a la población de estudiantes universitarios(as), las investigaciones se centran en cuantificar el problema de la violencia en la pareja (Esquivel-Santoveña et al, 2020;Lazarevich, Irigoyen-Camacho y Velázquez-Alva, 2017;López-Cepero, Estrada-Pineda y Chan-Gamboa, 2018;Rodríguez, Riosvelasco y Castillo, 2018). Por su parte, los estudios cualitativos indagan las creencias y actitudes de los(as) jóvenes en torno a la violencia de pareja (Rojas-Solís, 2013), así como las experiencias de las jóvenes como víctimas de esta clase de violencia (Vázquez y Castro, 2008).…”
Section: Introductionunclassified